Esprit De Corps among students: a case study in Institution of Teacher Education Rajang Campus (Institut Perguruan Rajang) / Mohd Suhardy Ujai and Boniface Selimah - Ujai, Mohd Suhardy; Selimah, Boniface (2013)
Every single person has their own perspective regarding team spirit. We are conducting a research in regard something that really normal happen in community especially students. ‘Esprit de Corps’ is a terms that we use on our research. It pictures the team spirit, team work, motivation to work as a team as well as motivation. By this, we would like to examine, the level of understanding regarding ‘Esprit de Corps’ among students. This is important because, students should know what are actually ‘Esprit de Corps’ so that they know how to work as a team as well as enhance their level of ‘Esprit de Corps’. Then, we also focused on individual perspective towards ‘Esprit de Corps’. This is important in order to define the perception of students regarding ‘Esprit de Corps’ as well as give a knowledge for them. Our study also focuses on the relationship between level of understanding and individual perspective regarding ‘Esprit de Corps’. By this, we manage to know, whether the individual perspective of ‘Esprit de Corps’ will affect the level of understanding of ‘Esprit de Corps’ among students.